2012
DOI: 10.1016/j.jcm.2011.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation under anesthesia for patients with failed back surgery: retrospective report of 3 cases with 1-year follow-up

Abstract: Three patients with failed back surgery were treated conservatively using MUA by trained chiropractic and osteopathic physicians followed by 8 weeks of post-MUA therapy. Pain and disability outcomes all improved immediately following treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…This case series, along with the others described above, [11][12][13][14][15][16][17][18][19] provides grade 4 evidence supporting the hypothesis that such treatment may also be safe and effective for patients experiencing spinal pain after spine surgery. When revision surgery is not indicated and nonpharmacologic treatment options are sought, spinal manipulation and/or mobilization is often considered.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This case series, along with the others described above, [11][12][13][14][15][16][17][18][19] provides grade 4 evidence supporting the hypothesis that such treatment may also be safe and effective for patients experiencing spinal pain after spine surgery. When revision surgery is not indicated and nonpharmacologic treatment options are sought, spinal manipulation and/or mobilization is often considered.…”
Section: Discussionsupporting
confidence: 58%
“…Kruse and Cambron 12 treated 32 postsurgical patients with flexion-distraction mobilization, reporting no adverse events and noting benefit in all patients regardless of surgical procedure used. Morningstar and Strauchman 13 treated 3 post-lumbar spine fusion patients with manipulation under anesthesia followed by 8 weeks of physical therapy, reporting durable subjective and functional improvement without adverse events; and Estadt 14 demonstrated positive response to a trial of lumbar manipulation and rehabilitative exercises in a patient who previously underwent lumbar microdiscectomy. Polkinghorn and Colloca 15 presented a single case of cervical spine pain post-discectomy and fusion that tolerated instrumental adjustment without adverse reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies report positive outcomes in treating the PSCP patient with chiropractic spinal manipulation. [36][37][38][39][40] Coulis and Lisi 41 reported on 3 cases (1 cervical, 2 lumbar) of PSCP. They reported that 15% to 61% of spine surgery patients report persistent or recurring pain postsurgically, with 2.3% to 12% of them presenting to chiropractic offices.…”
Section: Pscp Spinal Manipulation Clinical Treatment and Benefit Outcmentioning
confidence: 99%
“…The MUA procedure generally consists of sedation, mobilization/stretching/traction, manipulation, and post-MUA care. [15][16][17][21][22][23][24][25][26][27][28][29] Anesthesia minimizes pain, muscle spasm, and protective guarding that may occur during manipulation. Manipulation on a sedated patient is purported to enhance the practitioner's ability to break apart adhesions and repair segmental dysfunction, 11,15,17,30 leading to increased ligament, tendon, muscle, and articular flexibility.…”
Section: Introductionmentioning
confidence: 99%